2018
DOI: 10.1371/journal.pone.0204216
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of canine pancreatic lipase immunoreactivity and lipase activity in dogs with gastric dilatation-volvulus

Abstract: This study evaluated the association between a selection of candidate predictor variables, including the elevation of specific pancreatic enzymes, and outcome in dogs with gastric dilatation-volvulus (GDV).Twenty-two dogs with gastric dilatation-volvulus were included, being classified as survivors or non-survivors based on the final outcome. Dogs with intestinal obstruction (n = 16) were selected for comparison. Blood samples were collected upon admission (T0) and after 24 hours (T1). Serum lipase activity, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Pancreatic lipase concentrations are increased in several infectious diseases including parvovirus gastroenteritis, babesiosis, and monocytic ehrlichiosis 103‐106 . Pancreatic lipase concentrations also may be increased in dogs with intervertebral disc disease, foreign bodies and gastric‐dilatation and volvulus 49,107‐109 . These increases in pancreatic lipase concentration may be secondary effects on the exocrine pancreas associated with the primary disease condition.…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 99%
“…Pancreatic lipase concentrations are increased in several infectious diseases including parvovirus gastroenteritis, babesiosis, and monocytic ehrlichiosis 103‐106 . Pancreatic lipase concentrations also may be increased in dogs with intervertebral disc disease, foreign bodies and gastric‐dilatation and volvulus 49,107‐109 . These increases in pancreatic lipase concentration may be secondary effects on the exocrine pancreas associated with the primary disease condition.…”
Section: Pancreatic Lipase Concentrations In Dogs With Primary Diseases Other Than Pancreatitismentioning
confidence: 99%
“…Serum concentrations increase in dogs with systemic inflammation following surgery, trauma, infections, or neoplasia ( 21 ). Concentrations of CRP were commonly increased in dogs with GDV ( 7 , 22 , 23 ) and were significantly associated with a negative outcome in one study ( 24 ).…”
Section: Introductionmentioning
confidence: 95%
“…The 15-day mortality rate in this study was 20.7%. There is no comparable veterinary study with which to compare data, however, mortality rates reported in veterinary medicine for the most common surgical procedures encountered here, like gastrointestinal, hemoperitoneum or GDV syndrome surgeries, range from 0.8 to 28% [21][22][23][24][25][26], 12 to 36% [27,28] and 12 to 26 % [29][30][31][32][33][34][35][36], respectively.…”
Section: Discussionmentioning
confidence: 99%